THE IDENTITY OF THE TEACHING PROFESSIONAL: THEIR TRAINING AND REFLECTIONS IN THE STATE OF GOIÁS - Sotelo, Elcielle Rodrigues Carvalho; Caruso, Sérgio (Seven Editora, 2025)
This article analyzes the evolution of the professional identity of teachers and its relationship with initial and continuing education in the State of Goiás. It is based on the premise that teaching constitutes a socially and culturally mediated practice, whose knowledge is formed at the intersection of theory and practice. Teaching is not limited to the mere transmission of knowledge, but rather involves the formation of individuals for the progress and transformation of society. The research, of a bibliographic and documentary nature, is based on authors such as Gatti (2016), Nóvoa (1992, 2017), Pimenta (1999), Sacristán (1995), and Tardif (2002), as well as documents such as the National Education Plan (PNE) and the Goiás State Education Plan (PEE 2015–2025). Public policies and concrete working conditions shape teacher identity, and continuing education can act as a key element in professional development and career advancement for teachers. DOI: https://doi.org/10.56238/sevened2025.036-057